Systemic Infusion of Expanded CD133+ Cells and Expanded CD133+ Cell-Derived EVs for the Treatment of Ischemic Cardiomyopathy in a Rat Model of AMI - Addeli B. B. Angulski; Luiz Guilherme A. Capriglione; Fabiane Barchiki; Paulo Brofman; Marco A. Stimamiglio; Alexandra C. Senegaglia; Alejandro Correa (Hindawi Limited, 2019)
Myocardial infarction is a leading cause of death among all cardiovascular diseases. Cell therapies using a cell population enriched with endothelial progenitor cells (EPCs), expanded CD133+ cells, have promise as a therapeutic option for the treatment of ischemic areas after infarction. Recently, secreted membrane vesicles, including exosomes and microvesicles, have been recognized as new therapeutic candidates with important roles in intercellular and tissue communication. Expanded CD133+ cells have the ability to produce extracellular vesicles (EVs); however, their effect in the context of the heart is unknown. In the present study, we evaluated the effectiveness of the systemic application of expanded CD133+ cells and expanded CD133+ cell-derived EVs for the treatment of ischemic cardiomyopathy in a rat model of acute myocardial infarction (AMI) and examined the hypothesis that the EVs, because of their critical role in transferring regenerative signals from stem cells to the injured tissues, might elicit an equal or better therapeutic response than the expanded CD133+ cells. We demonstrate that the systemic application of expanded CD133+ cells and EVs has similar effects in infarcted rats. Few animals per group showed improvements in several heart and kidney parameters analyzed, but not significant differences were observed when comparing the groups. The systemic route may not be effective to treat ischemic cardiomyopathy; nonetheless, it may be a beneficial therapy to treat the side effects of AMI such as kidney damage.